Early strength agent for sprayed concrete and preparation method thereof

By preparing and adding early strength components, strengthening components, viscosity-increasing components, and scorching components, the problem of low strength in the early stage of sprayed concrete was solved, significantly improving the strength of 8 hours and 1 day, and reducing the rebound rate, meeting the rapid support needs of emergency projects.

CN119874247AActive Publication Date: 2025-04-25SHANDONG ZHONGYAN BUILDING MATERIALS TECH CO LTD +1

Patent Information

Application Number
CN202510002736.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-25
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The early strength of jet concrete is slow, and the existing rapid coagulant has low early strength within 8 hours and 24 hours, which cannot meet the rapid support needs of emergency projects.

Method used

By preparing early strength components, strengthening components, viscosity-increasing components, and scorching components, we promote cement condensation, accelerate the formation of early ettringite frameworks, increase the strength of 8 hours and 1 day of sprayed concrete, and reduce the rebound rate.

Benefits of technology

The 8-hour and 1-day strength of sprayed concrete is significantly improved, the viscosity is enhanced, the rebound rate is reduced, and the rapid support needs of emergency projects are met.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building material admixtures, in particular to an early strength agent for sprayed concrete and a preparation method of the early strength agent, and particularly, by preparing an early strength component, a reinforcing component, a tackifying and elasticity reducing component and a slump retaining component, cement setting is promoted, formation of an ettringite framework in the early stage of cement is accelerated, the 8-hour strength of the sprayed concrete is improved, and the service life of the sprayed concrete is prolonged. Meanwhile, the early strength of the cement is promoted to increase, the 1d strength of the sprayed concrete is remarkably improved, the cohesive force of the sprayed concrete can be improved, and the rebound rate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building material admixtures, in particular to an early strength agent for shotcrete and a preparation method thereof. Background Art

[0002] Tunnel projects are often encountered during the construction of infrastructure such as highways and high-speed railways. An important part of tunnel construction is support engineering construction. Sprayed concrete is a construction material commonly used in tunnel construction.

[0003] One of the biggest challenges facing shotcrete construction is the slow development of early strength. Although there are a variety of quick-setting agent products on the market that can meet the needs of rapid setting and hardening to a certain extent, the early strength of these products within 8 hours and 24 hours is still low, far from meeting the needs of rapid support in some emergency projects, which in turn affects the progress of tunnel construction.

[0004] At present, the way to improve early strength is to increase the amount of cement and other adhesives and add some traditional early strength agents to improve early strength, but the strength improvement is limited. Moreover, after adding traditional early strength agents, the concrete collapses severely and has poor time resistance, which brings troubles to construction. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides an early strength agent for shotcrete. Specifically, by preparing an early strength component, a reinforcing component, a viscosity-increasing and elastic-reducing component, and a collapse-preserving component, cement coagulation is promoted, the formation of an early cement ettringite framework is accelerated, the 8-hour strength of shotcrete is improved, and the early strength growth of cement is promoted, the 1d strength of shotcrete is significantly improved, and the cohesion of shotcrete can be improved and the rebound rate can be reduced.

[0006] Specifically, the early strength agent for shotcrete of the present invention is composed of the following raw materials in parts by weight: 50-75 parts of an early strength component, 30-50 parts of a reinforcing component, 0.5-4 parts of a viscosity-increasing and elastic-reducing component, and 2-5 parts of a collapse-preserving component.

[0007] Preferably, the early strength component preparation process is: limestone, montmorillonite, granite, bauxite, magnesium sulfate, lithium carbonate are mixed uniformly in a mass ratio of (20-25): (32-36): (19-21): (7-9): (7-9): (5-7), sintered at high temperature, cooled, ground to obtain fine powder, and fine powder and calcium silicate crystal nucleus are mixed uniformly in a mass ratio of (7-8): (2-3). The early components prepared by the present invention can promote cement coagulation, accelerate the formation of cement early ettringite framework, thereby improving the 8h compressive strength of shotcrete.

[0008] Preferably, the preparation process of the reinforcing component is: sodium carbonate, diethanolamine, and triethanolamine are mixed uniformly in a mass ratio of (4-6): (55-65): (15-25), heated to 120-130°C to obtain a mixed solution, 15-20% calcium oxide by mass of the mixed solution is added, stirred uniformly, cooled to obtain reinforcing powder, and reinforcing powder, magnesium sulfate, and calcium formate are mixed uniformly in a mass ratio of (13-16): (28-32): (50-60) to obtain. The reinforcing component prepared by the present invention is a powder, which can overcome the problems caused by the addition of triethanolamine in the form of a liquid, and the reinforcing component can accelerate the early hydration process of cement, promote the early strength growth of shotcrete, and significantly improve the 1d strength of shotcrete.

[0009] Preferably, the viscosity-increasing and elastic-reducing component is at least one of instant polyvinyl alcohol and nano-silicon dioxide. The viscosity-increasing and elastic-reducing component can increase the cohesion of the shotcrete, and combined with the use of the early strength component and the prior art quick-setting agent, the rebound rate of the shotcrete can be greatly reduced.

[0010] Preferably, the collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate, and macromonomer in a mass ratio of (18-22):(7-10):(28-32):360, and after vacuum drying, mixed with a retarder in a mass ratio of 1:(2-4). After sprayed concrete is wet-mixed with water, cement begins to hydrate. To ensure the construction of sprayed concrete, adding the collapse-preserving component of the present invention can reduce the fluidity loss caused by the rapid hydration of cement in the early stage.

[0011] The present invention can solve the shortcomings of shotcrete such as low early strength, large rebound rate, unstable setting time, etc. by cooperating the early strength component, reinforcing component, viscosity-increasing elasticity-reducing component, and collapse-preserving component.

[0012] More preferably, in the early strength component preparation process, magnesium sulfate and lithium carbonate are uniformly mixed in a mass ratio of 23:35:20:8:8:6.

[0013] More preferably, in the early strength component preparation process, sintering is performed at 900-950° C. for 3-4 hours.

[0014] More preferably, the particle size of the fine powder is ≤45 μm.

[0015] More preferably, in the process for preparing the reinforcing component, the mass ratio of sodium carbonate, diethanolamine and triethanolamine is 5:60:20.

[0016] More preferably, in the process for preparing the reinforcing component, the mass ratio of reinforcing powder, magnesium sulfate and calcium formate is 15:30:55.

[0017] More preferably, the collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate, and a macromonomer in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0018] More preferably, the macromonomer is at least one of TPEG, MPEG, and GPEG.

[0019] More preferably, the preparation process of the collapse-preserving component is:

[0020] ① Weigh 20 parts of acrylic acid, 30 parts of water, 8 parts of diallyl tartaric acid diamide, and 30 parts of hydroxyethyl acrylate, mix and add oil to obtain material A.

[0021] ② Weigh 0.5 parts of Vc, 60 parts of water, 2.1 parts of mercaptopropionic acid, and 2 parts of sodium bisulfite, mix well to obtain material B.

[0022] ③ Weigh 360 parts of macromonomer and 300 parts of water and mix them evenly, add 2 parts of flake caustic soda, 0.05 parts of ferrous sulfate, and 3 parts of hydrogen peroxide, mix evenly to obtain the base material.

[0023] ④ Add material A and material B to the base material at the same time, the adding time is 1.5h, keep warm for 0.5h, vacuum dry to obtain powder.

[0024] ⑤ Mix the powder and retarder in a ratio of 1:3.

[0025] More preferably, the retarder is at least one of sodium gluconate, borax, sucrose and sodium citrate.

[0026] The present invention also relates to a method for preparing the above-mentioned early strength agent for shotcrete, which specifically comprises the following steps:

[0027] 1) Weigh each raw material by mass,

[0028] 2) Evenly mix the early strength component, the reinforcing component, the viscosity-increasing and elastic-reducing component, and the collapse-preserving component to obtain the product.

[0029] The present invention also relates to the application of the early strength agent in the production and construction of shotcrete. Preferably, the early strength agent is added in an amount of 4-8% of the mass of the shotcrete cementitious material.

[0030] The present invention has the following technical advantages:

[0031] 1. The early strength agent for shotcrete of the present invention can improve the early strength of shotcrete, especially the 8h and 1d strength.

[0032] 2. The preparation process of the early strength agent for shotcrete of the present invention is simple, and it can be used together with the commercially available alkali-free quick-setting agent, and the use process is convenient.

[0033] 3. The early strength agent for shotcrete of the present invention can further reduce the rebound rate of shotcrete, and is suitable for the prevention and control of rock bursts and the spraying of seepage tunnel sections in mines, water conservancy projects, tunnels, and subways. It can meet the rapid support of emergency projects and the spraying process that conventional shotcrete cannot complete in seepage tunnel sections. DETAILED DESCRIPTION

[0034] In order to characterize the technical effect of the present invention, an early strength agent was prepared and its performance was tested. During the testing process, the early strength agent added in the embodiments and comparative examples was 6% of the mass of the cementitious material, and 6% of the mass of the cementitious material was added with a commercially available alkali-free quick-setting agent based on aluminum sulfate. The setting time of cement paste and the compressive strength of cement mortar were tested with reference to JC477-2005, and the rebound rate of mortar spraying construction was tested.

[0035] Example 1

[0036] The early strength agent is characterized in that it is composed of the following raw materials in parts by weight: 65 parts of early strength component, 40 parts of reinforcing component, 2.4 parts of viscosity increasing and elastic reducing component, and 3 parts of collapse retaining component.

[0037] The preparation process of the early strength component is as follows: limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are mixed uniformly in a mass ratio of 25:33:19:9:8:5, sintered at 950°C for 3h, cooled, ground to obtain fine powder, and the fine powder and calcium silicate crystal nuclei are mixed uniformly in a mass ratio of 8:2 to obtain.

[0038] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of 6:55:25, heated to 120° C. to obtain a mixed solution, 18% calcium oxide by mass of the mixed solution is added, stirred evenly, cooled to obtain reinforcing powder, and reinforcing powder, magnesium sulfate and calcium formate are mixed evenly in a mass ratio of 1:31:57 to obtain,

[0039] The viscosity-increasing and elastic-reducing component is instant polyvinyl alcohol,

[0040] The collapse-preserving component is polymerized by acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and TPEG in a mass ratio of 21:8:28:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:2.5.

[0041] After testing, the initial setting time of the net slurry was 3.6 minutes, the final setting time was 10.4 minutes, the 8-hour compressive strength was 4.0 MPa, the 1-day compressive strength was 15.3 MPa, and the vault rebound rate was 6.2%.

[0042] Example 2

[0043] The early strength agent is characterized in that it is composed of the following raw materials in parts by weight: 75 parts of early strength component, 45 parts of reinforcing component, 3 parts of viscosity increasing and elastic reducing component, and 2 parts of collapse retaining component.

[0044] The preparation process of the early strength component is as follows: limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are mixed uniformly in a mass ratio of 23:35:20:8:8:6, sintered at 900°C for 4 hours, cooled, ground to obtain fine powder, and the fine powder and calcium silicate crystal nuclei are mixed uniformly in a mass ratio of 7:3 to obtain.

[0045] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of 5:60:20, heated to 125° C. to obtain a mixed solution, 20% calcium oxide by mass of the mixed solution is added, stirred evenly, cooled to obtain reinforcing powder, and reinforcing powder, magnesium sulfate and calcium formate are mixed evenly in a mass ratio of 15:30:55 to obtain,

[0046] The viscosity-increasing and elastic-reducing component is nano-silicon dioxide.

[0047] The collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and MPEG in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0048] After testing, the initial setting time of the net slurry was 3.5 minutes, the final setting time was 9.3 minutes, the 8-hour compressive strength was 4.3 MPa, the 1-day compressive strength was 15.8 MPa, and the vault rebound rate was 5.8%.

[0049] Comparative Example 1

[0050] The early strength agent is characterized by being composed of the following raw materials in parts by weight: 75 parts of calcium chloride, 45 parts of reinforcing components, 3 parts of viscosity-increasing and elastic-reducing components, and 2 parts of collapse-preserving components.

[0051] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of 5:60:20, heated to 125° C. to obtain a mixed solution, 20% calcium oxide by mass of the mixed solution is added, stirred evenly, cooled to obtain reinforcing powder, and reinforcing powder, magnesium sulfate and calcium formate are mixed evenly in a mass ratio of 15:30:55 to obtain,

[0052] The viscosity-increasing and elastic-reducing component is nano-silicon dioxide.

[0053] The collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and MPEG in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0054] After testing, the initial setting time of the net slurry was 4.5 minutes, the final setting time was 11.0 minutes, the 8-hour compressive strength was 2.7 MPa, the 1-day compressive strength was 12.7 MPa, and the vault rebound rate was 12.4%.

[0055] Comparative Example 2

[0056] The early strength agent is characterized in that it is composed of the following raw materials in parts by weight: 75 parts of early strength component, 45 parts of reinforcing component, 3 parts of viscosity increasing and elastic reducing component, and 2 parts of collapse retaining component.

[0057] The preparation process of the early strength component is as follows: limestone, granite, bauxite and lithium carbonate are uniformly mixed in a mass ratio of 23:20:8:6, sintered at 900°C for 4 hours, cooled, and ground to obtain the early strength component.

[0058] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of 5:60:20, heated to 125° C. to obtain a mixed solution, 20% calcium oxide by mass of the mixed solution is added, stirred evenly, cooled to obtain reinforcing powder, and reinforcing powder, magnesium sulfate and calcium formate are mixed evenly in a mass ratio of 15:30:55 to obtain,

[0059] The viscosity-increasing and elastic-reducing component is nano-silicon dioxide.

[0060] The collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and MPEG in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0061] After testing, the initial setting time of the net slurry was 4.0min, the final setting time was 10.5min, the 8h compressive strength was 2.9MPa, the 1d compressive strength was 12.6MPa, and the vault rebound rate was 11.9%.

[0062] Comparative Example 3

[0063] The early strength agent is characterized in that it is composed of the following raw materials in parts by weight: 75 parts of early strength component, 45 parts of reinforcing component, 3 parts of viscosity increasing and elastic reducing component, and 2 parts of collapse retaining component.

[0064] The preparation process of the early strength component is as follows: limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are mixed uniformly in a mass ratio of 23:35:20:8:8:6, sintered at 900°C for 4 hours, cooled, ground to obtain fine powder, and the fine powder and calcium silicate crystal nuclei are mixed uniformly in a mass ratio of 7:3 to obtain.

[0065] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine, triethanolamine, magnesium sulfate and calcium formate are uniformly mixed in a mass ratio of 5:60:20:6:11 to obtain the reinforcing component.

[0066] The viscosity-increasing and elastic-reducing component is nano-silicon dioxide.

[0067] The collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and MPEG in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0068] After testing, the initial setting time of the net slurry was 4.1 minutes, the final setting time was 9.8 minutes, the 8-hour compressive strength was 3.5 MPa, the 1-day compressive strength was 10.4 MPa, and the vault rebound rate was 9.1%.

[0069] Comparative Example 4

[0070] The early strength agent is characterized in that it is composed of the following raw materials in parts by weight: 75 parts of early strength component, 45 parts of reinforcing component, 3 parts of viscosity increasing and elastic reducing component, and 2 parts of collapse retaining component.

[0071] The preparation process of the early strength component is as follows: limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are mixed uniformly in a mass ratio of 23:35:20:8:8:6, sintered at 900°C for 4 hours, cooled, ground to obtain fine powder, and the fine powder and calcium silicate crystal nuclei are mixed uniformly in a mass ratio of 7:3 to obtain.

[0072] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of 5:60:20, heated to 125° C. to obtain a mixed solution, 20% of the mass of the mixed solution by calcium oxide is added, stirred evenly, and cooled to obtain the mixture.

[0073] The viscosity-increasing and elastic-reducing component is nano-silicon dioxide.

[0074] The collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and MPEG in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0075] After testing, the initial setting time of the net slurry was 3.8 minutes, the final setting time was 10.6 minutes, the 8-hour compressive strength was 3.7 MPa, the 1-day compressive strength was 11.1 MPa, and the vault rebound rate was 9.5%.

[0076] Comparative Example 5

[0077] The early strength agent is characterized in that it is composed of the following raw materials in parts by weight: 75 parts of early strength component, 45 parts of reinforcing component, 3 parts of viscosity increasing and elastic reducing component, and 2 parts of collapse retaining component.

[0078] The preparation process of the early strength component is as follows: limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are mixed uniformly in a mass ratio of 23:35:20:8:8:6, sintered at 900°C for 4 hours, cooled, ground to obtain fine powder, and the fine powder and calcium silicate crystal nuclei are mixed uniformly in a mass ratio of 7:3 to obtain.

[0079] The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of 5:60:20, heated to 125° C. to obtain a mixed solution, 20% calcium oxide by mass of the mixed solution is added, stirred evenly, cooled to obtain reinforcing powder, and reinforcing powder, magnesium sulfate and calcium formate are mixed evenly in a mass ratio of 15:30:55 to obtain,

[0080] The viscosity-increasing and elastic-reducing component is nano-silicon dioxide.

[0081] The collapse-preserving component is polymerized by acrylic acid, acrylamide, hydroxyethyl acrylate and a macromonomer in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:3.

[0082] After testing, the initial setting time of the net slurry was 3.4 minutes, the final setting time was 9.8 minutes, the 8-hour compressive strength was 4.1 MPa, the 1-day compressive strength was 15.2 MPa, and the vault rebound rate was 8.2%.

[0083] Blank example

[0084] The blank example is compared with Example 2, except that no early strength agent is added in the blank example, and only 6% of the mass of the cementitious material is added with a commercially available alkali-free quick-setting agent based on aluminum sulfate.

[0085] After testing, the initial setting time of the net slurry was 4.9 minutes, the final setting time was 11.4 minutes, the 8-hour compressive strength was 2.4 MPa, the 1-day compressive strength was 10.6 MPa, and the vault rebound rate was 14.7%.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An early strength agent for shotcrete, characterized in that: It is composed of the following raw materials in parts by weight: 50-75 parts of early strength component, 30-50 parts of reinforcing component, 0.5-4 parts of viscosity increasing and elastic reducing component, 2-5 parts of collapse retaining component, The preparation process of the early strength component is as follows: limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are uniformly mixed in a mass ratio of (20-25):(32-36):(19-21):(7-9):(7-9):(5-7), sintered at high temperature, cooled, and ground to obtain fine powder; the fine powder and calcium silicate crystal nuclei are uniformly mixed in a mass ratio of (7-8):(2-3) to obtain, The preparation process of the reinforcing component is as follows: sodium carbonate, diethanolamine and triethanolamine are mixed evenly in a mass ratio of (4-6): (55-65): (15-25), heated to 120-130° C. to obtain a mixed solution, 15-20% of calcium oxide by mass of the mixed solution is added, stirred evenly, cooled to obtain reinforcing powder, reinforcing powder, magnesium sulfate and calcium formate are mixed evenly in a mass ratio of (13-16): (28-32): (50-60), and the obtained solution is obtained. The viscosity-increasing and elastic-reducing component is at least one of quick-soluble polyvinyl alcohol and nano-silicon dioxide. The collapse-preserving component is polymerized from acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate and a macromonomer in a mass ratio of (18-22):(7-10):(28-32):360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:(2-4).

2. The early strength agent for shotcrete according to claim 1, characterized in that: In the early strength component preparation process, limestone, montmorillonite, granite, bauxite, magnesium sulfate and lithium carbonate are evenly mixed in a mass ratio of 23:35:20:8:8:

6.

3. The early strength agent for shotcrete according to claim 1, characterized in that: In the early strength component preparation process, sintering is performed at 900-950° C. for 3-4 hours.

4. The early strength agent for shotcrete according to claim 1, characterized in that: The particle size of the fine powder is ≤45 μm.

5. The early strength agent for shotcrete according to claim 1, characterized in that: In the reinforcing component preparation process, the mass ratio of sodium carbonate, diethanolamine and triethanolamine is 5:60:

20.

6. The early strength agent for shotcrete according to claim 1, characterized in that: In the reinforcing component preparation process, the mass ratio of reinforcing powder, magnesium sulfate and calcium formate is 15:30:

55.

7. The early strength agent for shotcrete according to claim 1, characterized in that: The collapse-preserving component is polymerized by acrylic acid, diallyl tartaric acid diamide, hydroxyethyl acrylate, and a macromonomer in a mass ratio of 20:8:30:360, and after vacuum drying, is mixed with a retarder in a mass ratio of 1:

3.

8. The early strength agent for shotcrete according to claim 7, characterized in that: The preparation process of the collapse-preserving component is as follows: ① Weigh 20 parts of acrylic acid, 30 parts of water, 8 parts of diallyl tartaric acid diamide, and 30 parts of hydroxyethyl acrylate, mix and add oil to obtain material A. ② Weigh 0.5 parts of Vc, 60 parts of water, 2.1 parts of mercaptopropionic acid, and 2 parts of sodium bisulfite, mix well to obtain material B. ③ Weigh 360 parts of macromonomer and 300 parts of water and mix them evenly, add 2 parts of flake caustic soda, 0.05 parts of ferrous sulfate, and 3 parts of hydrogen peroxide, mix evenly to obtain the base material. ④ Add material A and material B to the base material at the same time, the adding time is 1.5h, keep warm for 0.5h, vacuum dry to obtain powder. ⑤ Mix the powder and retarder in a ratio of 1:

3.

9. The early strength agent for shotcrete according to claim 1, characterized in that: The retarder is at least one of sodium gluconate, borax, sucrose and sodium citrate.

10. The method for preparing the early strength agent for shotcrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by mass, 2) Evenly mix the early strength component, the reinforcing component, the viscosity-increasing and elastic-reducing component, and the collapse-preserving component to obtain the product.

Citation Information

Patent Citations

  • Concrete slump maintaining agent of polycarboxylate

    CN101066851A

  • High-early-strength low-resilience high-performance sprayed concrete and preparation method thereof

    CN114671644A

  • Coagulating early strength agent for sprayed concrete as well as preparation method and use method of coagulating early strength agent

    CN114873950A

  • Accelerator for concrete freeze protection

    KR1020170131773A

Cited By

  • Early-strength admixture of low-carbon sprayed concrete and preparation method of early-strength admixture

    CN121377589A

  • Low-carbon early strength admixture for shotcrete and preparation method thereof

    CN121377589B